The Impact of Guided Discovery Learning Model on Students’ Learning Outcomes on Temperature, Heat, and Expansion Topic - Saputri, Ernimel Diana; Tuti Lestari; Muttaqiin, Arief; Yanto, Febri (SEMESTA: Journal of Science Education and Teaching, 2025)
This research was driven by the observation that many students still lack a strong understanding of the subject matter, leading to below-average performance. Another factor that causes low student learning outcomes is the lack of variety in learning models applied by teachers so that learning becomes uninteresting. For this reason, various learning models are needed, such as the application of the guided discovery learning model The results of previous research stated that this model can improve student learning outcomes. This study aims to determine the effect of the application of the guided discovery learning model on students’ learning outcomes. This type of research is a quasi experiment with a nonequivalent control group design research design. The sampling technique uses the purposive sampling technique. The sample consists of one experimental class by applying the guided discovery learning model and one control class with a conventional model. This study conducted a statistical analysis using Microsoft Excel. The result shows that there is an improvement in students’ learning outcomes in the control class in the low category, while the increase in students’ learning outcomes in the experimental class is in the medium category.